EVALUATION OF IRON ORE FROM SOUTH KALIMANTAN AND TAILING OF PT. FREEPORT AS CATALYST PRECURSORS FOR DIRECT COAL LIQUEFACTION - MIFTAHUL HUDA; HERMANU PRIJONO; NINING S. NINGRUM; SUGANAL SUGANAL (Puslitbang tekMIRA, 2010)
Research on catalyst derived from minerals for coal liquefaction reaction remains attractive since Indonesia has various kinds of minerals which are suitable to be used as catalyst precursors. In this research, iron ore from South Kalimantan and tailing of PT. Freeport were examined their activities to find the most suitable catalyst precursor for coal liquefaction reaction. Experiments were performed using a 0.5 litre batch type autoclave equipped with a horizontal shaking unit (54 times per minute) at reaction temperature, initial hydrogen pressure and reaction time of 400oC, 10 MPa and 1 hr, respectively. The result showed that tailing produced lower oil yield and coal conversion than those of iron ore. Tailing is suspected to experience slower hydrogen transfer rate during coal liquefaction since it produced larger pyrrhotite crystal size than that of iron ore.